Cultural Ritual as Local Activity and Cultural Learning: Society of Padepokan Girijaya Village Girijaya - Sofia F Rahmani; Abd. Rahman Rahim; Eksa Rusdiyana; Avid Leonardo Sari (ijd-demos, 2022)
AbstractThis paper describes the seren year culture in society. In this Seren Year culture, it has its characteristics or uniqueness. The relationship between them is based on personal and mutual trust. This research also uses a descriptive method with a qualitative approach. The research results are the key to the success of a collaboration, which is strongly influenced by the size of the level of trust (radius of trust) established between the parties involved. Good communication will be easy to do, and cooperation can last a long time if it builds high values and norms of belief. Conversely, collaboration and culture will also be destroyed if they have low values and standards of faith. Thus the level of cooperation and high cultural traditions is closely related to how much value and trust norms are formed between the parties involved. And early childhood learning by teaching the art of aklung or nabeh from grade 1 elementary school is introduced until it is taught up to grade 6 elementary school with traditional self-taught methods and other skills.Keywords: culture, interaction, social capital, learning arts and culture  AbstrakTulisan ini menjelaskan tentang budaya tahun tenang di masyarakat. Dalam budaya Tahun Seren ini memiliki ciri khas atau keunikan tersendiri. Hubungan di antara mereka didasarkan pada kepercayaan pribadi dan timbal balik. Penelitian ini juga menggunakan metode deskriptif dengan pendekatan kualitatif. Hasil penelitian merupakan kunci keberhasilan suatu kolaborasi, yang sangat dipengaruhi oleh besar kecilnya tingkat kepercayaan (radius of trust) yang terjalin antara pihak-pihak yang terlibat. Komunikasi yang baik akan mudah dilakukan, dan kerjasama dapat bertahan lama jika membangun nilai dan norma kepercayaan yang tinggi. Sebaliknya, kolaborasi dan budaya juga akan hancur jika memiliki nilai dan standar keimanan yang rendah. Dengan demikian tingkat kerjasama dan tradisi budaya yang tinggi erat kaitannya dengan seberapa besar nilai dan norma kepercayaan yang terbentuk antara pihak-pihak yang terlibat. Dan pembelajaran anak usia dini dengan mengajarkan seni aklung atau nabeh dari kelas 1 SD diperkenalkan sampai diajarkan sampai kelas 6 SD dengan metode otodidak tradisional dan keterampilan lainnya.Kata kunci: budaya, interaksi, modal sosial, pembelajaran seni budaya